Dynamic alteration of intrinsic properties of the cerebellar Purkinje cell during the motor memory consolidation - Dong Cheol Jang; Geehoon Chung; Sun Kwang Kim; Sang Jeong Kim (Molecular Brain, 2023)
Abstract Intrinsic plasticity of the cerebellar Purkinje cell (PC) plays a critical role in motor memory consolidation. However, detailed changes in their intrinsic properties during memory consolidation are not well understood. Here, we report alterations in various properties involved in intrinsic excitability, such as the action potential (AP) threshold, AP width, afterhyperpolarization (AHP), and sag voltage, which are associated with the long-term depression of intrinsic excitability following the motor memory consolidation process. We analyzed data recorded from PCs before and 1, 4, and 24 h after cerebellum-dependent motor learning and found that these properties underwent dynamic changes during the consolidation process. We further analyzed data from PC-specific STIM1 knockout (STIM1PKO) mice, which show memory consolidation deficits, and derived intrinsic properties showing distinct change patterns compared with those of wild-type littermates. The levels of memory retention in the STIM1PKO mice were significantly different compared to wild-type mice between 1 and 4 h after training, and AP width, fast- and medium-AHP, and sag voltage showed different change patterns during this period. Our results provide information regarding alterations in intrinsic properties during a particular period that are critical for memory consolidation.